(untitled) (The New Uzbekistan Journal of Medicine, 2025)
Hemodynamics, the study of blood flow dynamics and the forces that govern it, is a fundamental aspect of understanding cardiovascular diseases (CVDs). This article delves into the application of hemodynamic principles in the diagnosis and management of CVDs, emphasizing blood pressure, flow velocity, and vascular resistance. Diagnostic techniques like echocardiography and catheterization are highlighted alongside treatments such as valve replacements and stenting. The insights derived from these principles pave the way for personalized treatment strategies, addressing conditions like hypertension, heart failure, and atherosclerosis.